Lateral Buckling Analysis of the Steel-Concrete Composite Beams in Negative Moment Region - Fengqi Guo; Shun Zhou; Lizhong Jiang (Advances in Materials Science and Engineering)
Distortional buckling is one of the important buckling models of steel-concrete composite beam in negative moment region. Rotation restraining rigidity and lateral restraining rigidity which steel beam web to bottom plate of steel-concrete composite are the key factors to influence the distortional buckling behavior. A comprehensive and intensive study on rotation restraining rigidity and lateral restraining rigidity which steel beam web to bottom plate of I-shaped steel-concrete composite beam in negative moment region is conducted in this paper. Energy variation principle is adopted to deduce the analytical expressions to calculate the rotation restraining rigidity and lateral restraining rigidity. Combined with the buckling theory of axial compression thin-walled bars in elastic medium, the buckling moment is obtained. Theoretical analysis shows that the rotation restraining rigidity and lateral restraining rigidity of steel beam web appear to have a linear relationship with the external loads and could also be negative. Compared with other methods, the results calculated by the proposed expressions agree well with the numerical results by ANSYS. The proposed expressions are more concise and suitable than the existing formulas for the engineering application.